2003
DOI: 10.1097/01.ju.0000068720.10881.b3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lidocaine Lubricant for Discomfort during Pediatric Urethral Catheterization

Abstract: The use of lubricant with lidocaine significantly decreases pain with pediatric urethral catheterization and is recommended with pediatric catheterizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 16 publications
0
52
0
3
Order By: Relevance
“…Despite the availability of effective topical analgesic agents for urinary catheterization, which is known to be pain and anxiety provoking, 27,28 60% of physicians in our study reported providing no analgesia for pediatric urinary catheterizations. Similarly, although IV insertion is known to cause moderate pain in infants and many options exist to limit this pain, 15,20,21,25,29 only half of physicians reported that they ''often or always'' used analgesia for venipuncture.…”
Section: Discussionmentioning
confidence: 64%
“…Despite the availability of effective topical analgesic agents for urinary catheterization, which is known to be pain and anxiety provoking, 27,28 60% of physicians in our study reported providing no analgesia for pediatric urinary catheterizations. Similarly, although IV insertion is known to cause moderate pain in infants and many options exist to limit this pain, 15,20,21,25,29 only half of physicians reported that they ''often or always'' used analgesia for venipuncture.…”
Section: Discussionmentioning
confidence: 64%
“…This uncertainty may be explained by the conflicting results of pediatric trials of topical analgesia. These inconsistencies could be due to suboptimal application times, restraining the infant, small sample sizes, 21,22 or exclusively topical administration. 23 The importance of providing optimal pain treatment is echoed by both the World Health Organization 24 and the American Academy of Pediatrics, 25 who recently reaffirmed its advocacy for adequate analgesia for painful procedures in children.…”
Section: What This Study Addsmentioning
confidence: 99%
“…O traumatismo uretral pode ser minimizado através de medidas simples, todavia de grande impacto, representadas pelo uso de lubrificantes, escolha e manuseio de materiais adequados para a introdução e fixação do cateter, além de cuidados com o balonete (MIRANDA et al, 2006;NEWMAN 2007;LEUCK et al, 2012 (DEVINE, 2003;AARONSO et al, 2008;GRAY, 2008;KASHEFI et al, 2008;TZORTZIS et al, 2009;WILLSON et al, 2009;FAKIH et al, 2010;GORDETSKY et al, 2011 (TANABE et al, 2004), de 0,5 a 2 ml e cerca de 2 a 3 minutos em lactentes e 0,5 a 2 ml e cerca de 10 minutos em crianças acima de um ano (GERARD et al, 2003;VAUGHAN et al, 2005).…”
Section: Trauma Uretralunclassified
“…Preconiza-se que sejam utilizados no homem cerca de 10 ml de lubrificante, na mulher 6 ml e na criança de 0,5 a 2 ml há depender da sua idade. (GERARD et al 2003;VAUGHAN et al, 2005;MAZZO et al, 2012). Ainda sobre o assunto cabe salientar que se preconiza o uso de sistema fechado na introdução do cateter como forma de prevenção de infeção do trato urinário.…”
Section: Etapaunclassified
See 1 more Smart Citation